2013
DOI: 10.1007/s00464-013-3204-0
|View full text |Cite
|
Sign up to set email alerts
|

Revisional versus primary Roux-en-Y gastric bypass: a case-matched analysis

Abstract: Revisional laproscopic VVLL RYGB can be performed as a one-stage procedure by experienced bariatric surgeons but shows less effective EWL than primary RYGB procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…The reason for this difference remains unclear, though some speculate that it is because the patients requiring revisional bariatric surgery for inadequate weight loss may have poor diet compliance that resulted in their need for secondary surgery. Another possibility may be that the physiologic change of energy metabolism may be different for a secondary bariatric surgery than primary bariatric surgery [22]. Brolin et al showed that percent weight loss is even dependent on the type of primary bariatric surgery performed [23].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference remains unclear, though some speculate that it is because the patients requiring revisional bariatric surgery for inadequate weight loss may have poor diet compliance that resulted in their need for secondary surgery. Another possibility may be that the physiologic change of energy metabolism may be different for a secondary bariatric surgery than primary bariatric surgery [22]. Brolin et al showed that percent weight loss is even dependent on the type of primary bariatric surgery performed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies have shown inferior weight loss with RBS [2][3][4], others have not. At the same time, some authors [5,6] have shown that inferior weight loss with RBS does not come at the cost of inferior comorbidity resolution.…”
Section: Introductionmentioning
confidence: 95%
“…Most studies that assessed the effectiveness of P-RYGB and R-RYGB only examined the weight loss and surgical complications [12][13][14]. Moreover, these studies reported inconsistent findings, suggesting comparable weight loss and complications for patients who underwent P-RYGB and R-RYGB [12][13][14] or inferior weight loss and higher complications in patients who received R-RYGB [15,16]. Furthermore, few studies have assessed the evolution of comorbidities after P-RYGB and R-RYGB [8,17,18], despite the possibility of relapse of comorbidities after RYGB (e.g., T2DM, HTN, and dyslipidemia).…”
Section: Introductionmentioning
confidence: 99%